Effect of statins on the risk of recurrent venous thromboembolism: A systematic review and meta-analysis. (March 2021) - Li, Ruihao; Yuan, Manqiu; Yu, Shixiong; Fu, Wenlong; Yu, Wu; Ling, Siying; Sun, Jianming; Chen, Yikuan
Graphical abstract: Highlights: The effect of statins on risk of recurrent venous thromboembolism (VTE) was systematically analyzed. Statins were associated with lower risks of recurrent VTE and its two forms, i.e. DVT and PE. Statins were associated with a lower risk of mortality among patients with VTE. Randomized clinical trials are warranted to corroborated these findings. Abstract: Background: Recent studies have suggested that statins may be associated with a lower risk of recurrent venous thromboembolism (VTE). Methods: We systematically searched PubMed, Web of Science and Cochrane Library from inception until May 2020 to identify any eligible studies that reported the association between statin use and the risk of recurrent VTE, and conducted a comprehensive systematic review and meta-analysis (PROSPERO registration number: CRD42020190169) on this matter. Results: A total of 14 observational studies were included for qualitative review and 12 of them qualified for meta-analyses. The main meta-analysis found that statin use was associated with a lower risk of disease recurrence among patients with VTE (pooled adjusted HR: 0.76, 95% CI: 0.69−0.83), which was robust in sensitivity analyses and free of significant publication bias. Additionally, such association was present when restricting to periods after anticoagulation withdrawal (pooled adjusted HR: 0.78, 95% CI: 0.70−0.88) and when separately analyzing recurrent deep vein thrombosis (pooled adjusted HR: 0.71, 95% CI: 0.62−0.81) and recurrent pulmonary embolism (pooled adjusted HR: 0.80, 95% CI: 0.66−0.97; P = 0.027). Furthermore, statin use in patients with VTE was also found to be associated with a lower risk of all-cause mortality (adjusted HR: 0.65, 95% CI: 0.56−0.77), and possibly an even lower risk of bleeding (adjusted HR: 0.88, 95% CI: 0.73–1.07), albeit not statistically significant. Conclusion: Statins have the potential to reduce recurrent events among patient with VTE. Randomized clinical trials to better explore the effect of statins in secondary prevention of VTE are warranted.